1987
DOI: 10.1055/s-2008-1025641
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Lactic Anaerobic Metabolism in Handballers

Abstract: The authors investigated lactic anaerobic metabolism in handball players during practice games. Seven players aged 18-21, belonging to second division league clubs, took part in the study. In the laboratory, VO2 max and the onset of blood lactate accumulation (OBLA) were determined with progressive maximal ergocycle tests. On the field, video recordings, cardiotelemetry, and rectal temperature measurements made during the first half of the game were used to quantify exertion. An intravenous catheter worn perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 11 publications
2
32
1
7
Order By: Relevance
“…Nevertheless, significant differences between groups were observed in five physiological evaluations, i.e. the successful team-handball athletes recorded (i) higher values for sit-ups, (ii) faster times over the 30-m sprint, and (iii) lower values on dynamometry tests (handgrip 27 has reached the conclusion that the maximal aerobic power and capacity are prerequisites to the achievement of excellence in team-handball (age 18---21 years), and more recently Gorostiaga et al 28 concluded that endurance capacity does not seem to be a limiting factor for elite performance in team-handball. In fact, our results suggest that team-handball players may not need to have an extraordinary aerobic capacity, but they must possess a reasonably high level aerobic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, significant differences between groups were observed in five physiological evaluations, i.e. the successful team-handball athletes recorded (i) higher values for sit-ups, (ii) faster times over the 30-m sprint, and (iii) lower values on dynamometry tests (handgrip 27 has reached the conclusion that the maximal aerobic power and capacity are prerequisites to the achievement of excellence in team-handball (age 18---21 years), and more recently Gorostiaga et al 28 concluded that endurance capacity does not seem to be a limiting factor for elite performance in team-handball. In fact, our results suggest that team-handball players may not need to have an extraordinary aerobic capacity, but they must possess a reasonably high level aerobic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…Alguns estudos (6,7,9) foram realizados com o intuito de determinar a capacidade aeróbia de atletas de handebol, no entanto, nenhum deles apresentou os resultados referentes ao limiar anaeróbio (km.h -1 ). Delamarche et al (9) constataram em cicloergômetro que o consumo de oxigênio no OBLA (Onset of Blood Lactate Concetration) foi de 3,53 ± 0,22 L.min -1 .…”
Section: Pmáx (W) Pmédia (W) Pmín (W)unclassified
“…Delamarche et al (9) constataram em cicloergômetro que o consumo de oxigênio no OBLA (Onset of Blood Lactate Concetration) foi de 3,53 ± 0,22 L.min -1 . Gorostiaga et al (6) estudaram o efeito de 6 semanas de treinamento de resistência nas concentrações de lactato sanguíneo referentes as velocidades de 10 e 11 km.h -1 em handebolistas adolescentes (15,1 ± 0,7 anos).…”
Section: Pmáx (W) Pmédia (W) Pmín (W)unclassified
See 2 more Smart Citations